The yellow shawl an adaptation of a short story into contemporary dance interpreted through symbols and imageries - Torte, Ma. Alexa Andrea R.
The study aims to serve as a guide and as future reference for students majoring in dance, and choreographers who are planning to create a dance production through the process of adaptation. To determine the choreographic style, symbols, and methods used in "The Yellow Shawl"; To document the overall artistic and production process; To understand how collaboration took place in creating the production.